Analisis Kinerja Keuangan Pada PT PLN (Persero) Distribusi Jawa Barat dan Banten - Masruroh Masruroh; Ignasius Dwi Martito Nugroho (STIE Indonesia Banking School, 2016)
The research objective would like to know the analysis of financial statements to assess the performance of the company at PT PLN (Persero) Distribusi Jawa Barat dan Banten. The research method is a method of time series analysis, which is done by comparing the financial statement for several years (period) so that it can be seen in developments and trends. Analysis using ratio analysis can provide an assessment of the company’s financial performance, terms of the ratio of liquidity, solvency and profitability as well as it’s financial performance target are given from PT PLN Kantor Pusat, among others Biaya Pokok Penyediaan (BPP), OPEX Non Fuel, Umur Piutang Pelanggan (COP), Pertumbuhan Penjualan, Penyerapan Disburse Investasi APLN, Pengadaan Kendaraan Listrik dan Biaya Administrasi per Pelanggan. The data used are secondary data which includes the company’s financial balance sheet and income statement for three (3) years 2011-2013. Conclude the performance of PT PLN (Persero) Distribusi Jawa Barat dan Banten viewed from the perspective of the general financial performance achievement in 2012 is better than in 2013 and 2011, while the achievement of the performance of the year 2013 at the lower of the two periods in 2011 and 2012 related to the change in policy and a good rule of the rule of the central government or Kantor Pusat PLN